The Influence of Word of Mouth, Taste Quality, and Promotion on Purchasing Decisions for Snacks Through Digital Media - Rosita Noviana; Jasmine Chiquita Brilliana; Nadya Kamilia Fai’qoh; Asty Dwinanda Putri; Safira Fathin (Unversitas Muhammadiyah Mataram, 2024)
Abstract: Digital technologies such as social media and e-commerce are used to promote and sell MSME products, including in the culinary industry. The packaged food and beverage industry is experiencing development in Indonesia, as shown by the increasing number of sales, especially snack foods in the form of snacks and crackers. Research was conducted to see the influence of word of mouth, product quality, and promotions on purchasing decisions to purchase snack products through digital media. The survey results from 196 respondents selected using a simple random sampling method with several criteria were then analyzed using a multiple linear regression test using SPSS. The regression analysis showed that the t-value and f-value of word of mouth, product quality, and promotion are more significant than the t-table and f-table, with a significance value of less than 0.05. This illustrated that word of mouth, taste quality, and promotion significantly influence purchasing snack products via digital media. This indicated that MSMEs can use Tokopedia to increase snack sales.